A new species of Tyrannomyrmex (Hymenoptera: Formicidae) from Sri Lanka - Alpert, Gary D. (Zootaxa, 2013)
Tyrannomyrmex legatus sp. nov. is described based on a single worker collected from leaf litter in dipterocarp forest in southern Sri Lanka. A key is presented to separate the three known species of Tyrannomyrmex. A probable male specimen of the genus from the Philippines is noted. Tyrannomyrmex is placed within the tribe Solenopsidini and close to the genus Monomorium.